The SCFSlimb E3 ligase complex regulates asymmetric division to inhibit neuroblast overgrowth. (10th January 2014) - Li, Song; Wang, Cheng; Sandanaraj, Edwin; Aw, Sherry S Y; Koe, Chwee T; Wong, Jack J L; Yu, Fengwei; Ang, Beng T; Tang, Carol; Wang, Hongyan
Synopsis <boxed-text content-type="graphic" id="embr201337966-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> This report provides evidence that loss of the SCFSlimb E3 ubiquitin ligase complex as well as hyperactivation of Akt lead to neuroblast overgrowth and defects in asymmetric cell division. Slimb, the F‐box protein of the SCF complex, associates with Akt in a protein complex, and SCFSlimb acts through SAK and Akt to inhibit neuroblast overgrowth. The SCFSlimb E3 ubiquitin ligase inhibits neuroblast (NB) overgrowth and regulates asymmetric division of NBs. The NB overgrowth phenotype in the absence of SCFSlimb is similar to what is seen in conditions of AKT hyperactivation. The F‐box protein Slimb associates with AKT and regulates NB overgrowth via SAK and AKT.